Mesenchymal Stromal Cells in Animal Bleomycin Pulmonary Fibrosis Models: A Systematic Review. (22nd October 2015) - Srour, Nadim; Thébaud, Bernard
Abstract : Data from 17 animal studies indicated mesenchymal stromal cell (MSC) therapy led to improvement in bleomycin-induced lung collagen deposition, pulmonary fibrosis Ashcroft score (in most studies), histopathology, 14-day survival in animal models, and reduced levels of markers of inflammation. Preclinical data offer better support for human trials of MSCs in acute exacerbations rather than the chronic phase of pulmonary fibrosis. Abstract: : Idiopathic pulmonary fibrosis is an inexorably progressive lung disease with few available treatments. New therapeutic options are needed. Stem cells have generated much enthusiasm for the treatment of several conditions, including lung diseases. Human trials of mesenchymal stromal cell (MSC) therapy for pulmonary fibrosis are under way. To shed light on the potential usefulness of MSCs for human disease, we aimed to systematically review the preclinical literature to determine if MSCs are beneficial in animal bleomycin pulmonary fibrosis models. The MEDLINE and Embase databases were searched for original studies of stem cell therapy in animal bleomycin models of pulmonary fibrosis. Studies using embryonic stem cells or induced pluripotent stem cells were excluded. Seventeen studies were selected, all of which used MSCs in rodents. MSC therapy led to an improvement in bleomycin-induced lung collagen deposition in animal lungs and in the pulmonary fibrosis Ashcroft score in most studies. MSC therapy improved histopathology in almost all studies in which it was evaluated qualitatively. Furthermore, MSC therapy was found to improve 14-day survival in animals with bleomycin-induced pulmonary fibrosis. Bronchoalveolar lavage total and neutrophil counts, as well as transforming growth factor-β levels, were also reduced by MSCs. MSCs are beneficial in rodent bleomycin pulmonary fibrosis models. Since most studies examined the initial inflammatory phase rather than the chronic fibrotic phase, preclinical data offer better support for human trials of MSCs in acute exacerbations of pulmonary fibrosis rather than the chronic phase of the disease. Significance: There has been increased interest in mesenchymal stromal cell therapy for lung diseases. A few small clinical trials are under way in idiopathic pulmonary fibrosis. Preclinical evidence was assessed in a systematic review, as is often done for clinical studies. The existing studies offer better support for efficacy in the initial inflammatory phase rather than the fibrotic phase that human trials are targeting.